Upaya Optimalisasi Kualitas Pelayanan Publik dalam Pelayanan Kartu Tanda Penduduk Elektronik di Kantor Kecamatan Gedangan - Haryono, Haryono; Pujianto, Wahyu Eko (Universitas Muhammadiyah Sidoarjo, 2013)
This study aimed to identify and describe the effort of public service to optimize quality on electronic ID card in Gedangan sub-district office. Electronic ID CARD or e-ID CARD is a document demography who loads the security system/good control of the sides of the administration of or information technology based on database demography national. Inhabitant only allowed having 1 (one) KTP that is listed number the parent demography (NIK). NIK is identity any inhabitant of and force a lifetime. The method of this study used a qualitative approach. Based on the research results showed that the optimization of the ID card services in Sidoarjo has been done through the realization of the socialization of local government in the process of making the e-ID card was free charge. This suggests that socialization in Sidoarjo Regency significantly withcommunity goals in Gedangan Sub-district particularly to carry out their duty as Indonesia citizens.